Food Processing and Packaging Technologies - Recent Advances 2023
DOI: 10.5772/intechopen.108666
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Food Antimicrobial Packaging

Abstract: Acutely due to awareness that food products are highly vulnerable to microbial contamination, the food industry constantly tries to uncover new methods for the preservation of their products in order to guarantee their goods and processes continue to offer the highest quality and uphold safety standards throughout the production, storage, and distribution chain. Antimicrobial food packaging can play an important role in food shelf-life extension through the inhibition of microorganism growth present on the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…Active packaging materials, such as coated films or paper, for short time storage can be the ideal solution to this problem. These materials should be covered with coatings containing natural substances, such as plant extracts, which act as antimicrobial compounds [10,22]. The results of the current work showed that MHPC coating containing 50% of the S. baicalensis* and Glycyrrhiza L. extracts (in m1-1*:2 ratio) mixture inhibited the growth of mesophilic bacteria for sliced chicken sausages that were stored for 72 h and decreased their number after 144 h of storage.…”
Section: Discussionmentioning
confidence: 66%
“…Active packaging materials, such as coated films or paper, for short time storage can be the ideal solution to this problem. These materials should be covered with coatings containing natural substances, such as plant extracts, which act as antimicrobial compounds [10,22]. The results of the current work showed that MHPC coating containing 50% of the S. baicalensis* and Glycyrrhiza L. extracts (in m1-1*:2 ratio) mixture inhibited the growth of mesophilic bacteria for sliced chicken sausages that were stored for 72 h and decreased their number after 144 h of storage.…”
Section: Discussionmentioning
confidence: 66%
“…The most widespread strawberry pathogens are Fusarium oxysporum, Phytophthora fragariae, Colletotrichum acutatum, Verticillium dahliae, Botrytis cinerea, Macrophomina phaseolina, Xanthomonas fragariae, Rhizopus stolonifer and Penicillium expansum, Cladosporium sp. [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Edible coatings, when applied as a thin layer on the surface of food products, act as a barrier against gases, vapors and solutes and may maintain food quality at a high level. They may potentially extend the shelf-life through the reduction of microorganisms responsible for fruit decay [6][7][8]. The active agents can also be incorporated into the packaging material [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations